SAS Method assisted by Picture Story Books to Improve Elementary School Students' Beginning Reading Ability - Rahayu, Lia; Daud, Ridhwan M (Journal of Indonesian Primary School, 2024)
Reading ability is one of the language skills that every student must master. To a certain extent, reading ability becomes a basic ability that can be used to analyze certain information or data. This research aims to improve elementary school students' initial reading abilities. The type of research used is classroom action research. The subjects of this research were elementary school students. Data collection was carried out using observation and test techniques. The data obtained was then analyzed using descriptive statistical techniques. The research results show that the SAS method assisted by picture story books can improve elementary school students' initial reading abilities. This can be seen from the results of the first cycle which reached 65.38%, then increased in the second cycle to 76.92% and finally to 84.61% in the third cycle. Below is a diagram of the achievements in each cycle. Therefore, the SAS method assisted by picture story books can be used as a reference that can be used in learning Indonesian at the elementary school level, especially in terms of improving beginning reading skills